2015
DOI: 10.15713/ins.ijdhc.4
|View full text |Cite
|
Sign up to set email alerts
|

Face and Content Validation of Caries Assessment Spectrum and Treatment Index among Few Subject Matter Experts in India

Abstract: Introduction:The proposed new index by Dr. Frencken: Caries Assessment Spectrum and Treatment (CAST) Index. It addresses the assessment of clinical stages of carious lesion progression in enamel, dentine, pulp and cavity restored under 9 codes. Content validity as a part of psychometric testing was conducted by Frencken in Brazil, which included 15 countries and India was not included. Hence, the aim of this study was to assess the face and content validity of CAST Index in India. Materials and Methods: Face a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…CAST index to certain extent has shown a promising index for caries epidemiology as it depicts the full range of carious lesions and is also simple, inexpensive, and less time-consuming. [ 14 ] But while conducting its validation for use on the Indian population by Phansopkar S et al ,[ 13 ] he suggested that some modifications are required for its use in a diverse country like India for epidemiological purposes. Hence, we developed Agrawal and Shah modified CAST index [ Table 1 ] that would be more applicable for the caries assessment in epidemiological surveys in India.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CAST index to certain extent has shown a promising index for caries epidemiology as it depicts the full range of carious lesions and is also simple, inexpensive, and less time-consuming. [ 14 ] But while conducting its validation for use on the Indian population by Phansopkar S et al ,[ 13 ] he suggested that some modifications are required for its use in a diverse country like India for epidemiological purposes. Hence, we developed Agrawal and Shah modified CAST index [ Table 1 ] that would be more applicable for the caries assessment in epidemiological surveys in India.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 11 12 ] Face and content validation of the CAST index was done by their proposers in 15 different countries, including Canada, Chile, South Africa, Brazil, Tanzania, Nigeria, Iraq, Mexico, Turkey, Germany, Finland, Australia, China, and Thailand, but India was excluded. [ 10 ] In India, this was attempted by Phansopkar S et al ,[ 13 ] and they found that the CAST index can be considered for epidemiological surveys in India but with some changes in the original index. Henceforth, we have done addition, deletion, or modifications required in the original CAST index and proposed “Agrawal and Shah modified CAST index” for assessing dental caries prevalence and treatment needs of the Indian population [ Table 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…10 The previous study has demonstrated CAST Index to be a good instrument in epidemiological surveys in India after a couple of modifications of the original index. 13 Its application regarding Indian context can be justified considering the varied population with different socioeconomic and cultural backgrounds and the fact that entire dental caries spectrum can be recorded at once using CAST index. 13 In this study, barely 35% had permanent teeth that were caries free.…”
Section: Discussionmentioning
confidence: 99%
“…13 Its application regarding Indian context can be justified considering the varied population with different socioeconomic and cultural backgrounds and the fact that entire dental caries spectrum can be recorded at once using CAST index. 13 In this study, barely 35% had permanent teeth that were caries free. No children had preventive fillings in permanent teeth and only 9% had fillings.…”
Section: Discussionmentioning
confidence: 99%
“…The PUFA index covers the carious lesions involving the pulp and peri-apical tissues but not the initial caries attack to enamel and dentine. [15] In contrast, the CAST Index integrates the various stages of carious lesion progression and abscesses/fistulae as well as preventive and restorative care in a single-digit coding system. [15] It also gives the advantage of deriving the DMFT score out of it and hence making statistical analysis and comparison with previously done studies using DMFT index much easier.…”
mentioning
confidence: 99%